Late stillbirth post mortem examination in New Zealand: Maternal decision‐making. (5th March 2018) - Cronin, Robin S.; Li, Minglan; Wise, Michelle; Bradford, Billie; Culling, Vicki; Zuccollo, Jane; Thompson, John M. D.; Mitchell, Edwin A.; McCowan, Lesley M. E.
Abstract : Background: For parents who experience stillbirth, knowing the cause of their baby's death is important. A post mortem examination is the gold standard investigation, but little is known about what may influence parents' decisions to accept or decline. Aim: We aimed to identify factors influencing maternal decision‐making about post mortem examination after late stillbirth. Methods: In the New Zealand Multicentre Stillbirth Study, 169 women with singleton pregnancies, no known abnormality at recruitment, and late stillbirth (≥28weeks gestation), from seven health regions were interviewed within six weeks of birth. The purpose of this paper was to explore factors related to post mortem examination decision‐making and the reasons for declining. We asked women if they would make the same decision again. Results: Maternal decision to decline a post mortem (70/169, 41.4%) was more common among women of Māori (adjusted odds ratio (aOR) 4.99 95% confidence interval (CI) 1.70–14.64) and Pacific (aOR 3.94 95% CI 1.47–10.54) ethnicity compared to European, and parity two or more (aOR 2.95 95% CI 1.14–7.62) compared to primiparous. The main reason for declining was that women 'did not want baby to be cut'. Ten percent (7/70) who declined said they would not make this decision again. No woman who consented regretted her decision. Conclusion: Ethnic differences observed in women's post mortem decision‐making should be further explored in future studies. Providing information of the effect of post mortem on the baby's body and the possible emotional benefits of a post mortem may assist women faced with this decision in the future.